Abstraksi Gerak Anjing Dalam Penciptaan Karya Seni Patung - Artha Adi Wijaya, I Nengah; Udiana Nindhia Pemayun, Tjokorda; Yosef Tjokropramono, Gede (Program Studi Seni Murni ISI Bali, 2022)
Dogs are social animals, but the personality and behavior of dogs can vary depending on the breed. In addition, the dog's personality depends on the treatment it receives from the dog and the people who interact with it frequently. From the dog's personality, it is interesting to be appointed as the object of internship at CV. Richstone. The author realizes the work of sculpture by observing the dog's movements by abstracting the dog's movements from various points of view by using line and plane composition to achieve visualization of the work. The process of making the work uses a cast iron frame first using cast concrete, followed by the addition technique in which the cast frame of the statue is wrapped with burlap sacks on the entire frame of the statue. In visualization the work displays two dog figure movements which are abstracted by the presentation not directly, but using non-representational forms or more depicting the shape of the objects depicted which are often difficult to grasp for meaning by ordinary observers/art connoisseurs, the first work with dynamic dog movements running and the second work with the movements of a frightened dog.